Clustering in the UK financial services: The quest for the enigmatic pecuniary externality - Adrian Kuah (The University of Manchester, Manchester Business School, 2008)
This paper explores the sources of agglomeration externalities in enhancing firm performance, in particular, the pecuniary externality that supports firms' bottom line. The fundamental argument on increasing returns leads to the premise that cluster size has beneficial influence to firm performance. However, recent arguments suggest that diseconomies may set in and the agglomeration of related sectors in a cluster lead to congestion that is detrimental to firm performance. The enigmatic pecuniary externality is under-researched but often discussed. In this research, the role of related sectors in boosting the member firm's financial performance is revealed through a cross-section data of some 17,000 financial services companies in the UK.
Keywords: 330; financial services; externalities; industry cluster; UK regions and competitiveness; Clusteranalyse; Agglomerationseffekt; Finanzdienstleistung; Finanzsektor; Großbritannien